2015
DOI: 10.1037/a0039600
|View full text |Cite
|
Sign up to set email alerts
|

Positive school climate as a resilience factor in armed conflict zones.

Abstract: Objective: Although schools have a meaningful effect on students' lives, their role as a resilience factor for students experiencing ethno-political violence has never been studied. The aim of the present study was to investigate the contribution of students' school experience, and the school climate in particular, to students' coping with violence, and specifically its effect on the development of posttraumatic stress disorder (PTSD) and posttraumatic growth (PTG). Method: A cross-sectional telephone question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
2
17
1
1
Order By: Relevance
“…Inconsistent with our hypothesis, we found that the one-step (via feelings of safety) and two-step (through feelings of safety via cognitive reappraisal) indirect effects of parental attachment on PTG were nonsignificant. This could be attributable to the nonsignificant direct relationship of feelings of safety to PTG and cognitive reappraisal in this study; findings inconsistent with previous studies (Najavits, Weiss, Shaw, & Muenz, 2010;Tavakol, Chen, Zook, & Bethea, 2015;Yablon, 2015). A possible explanation is that perceived safety induces individuals' cognitive activity and, in turn, leads to post-traumatic reactions (e.g.…”
Section: Discussioncontrasting
confidence: 98%
“…Inconsistent with our hypothesis, we found that the one-step (via feelings of safety) and two-step (through feelings of safety via cognitive reappraisal) indirect effects of parental attachment on PTG were nonsignificant. This could be attributable to the nonsignificant direct relationship of feelings of safety to PTG and cognitive reappraisal in this study; findings inconsistent with previous studies (Najavits, Weiss, Shaw, & Muenz, 2010;Tavakol, Chen, Zook, & Bethea, 2015;Yablon, 2015). A possible explanation is that perceived safety induces individuals' cognitive activity and, in turn, leads to post-traumatic reactions (e.g.…”
Section: Discussioncontrasting
confidence: 98%
“…Guided by ecological resilience theory, the current study examines whether three dimensions of school climate (i.e., safety, connectedness, services) serve as protective factors in the relations between exposure to violence and externalizing behaviors and developmental competence. Prior research has found that school climate has important protective implications for violence‐affected youth (O'Donnell, Roberts, & Schwab‐Stone, ; Yablon, ). More research is needed, however, in additional contexts and with more nuanced measures of school climate to identify ways in which schools can improve outcomes for adolescents exposed to violence.…”
Section: Introductionmentioning
confidence: 99%
“…Schools, and particularly the quality of a school's climate (Bradshaw, Waasdorp, Debnam, & Lindstrom Johnson, ), have been identified as important ecological contexts for building resilience. Limited research has studied the importance of school climate for adolescents affected by both political and community violence (for exceptions, see Benbenishty & Astor, ; Yablon, ). In Colombia, adolescents’ perceptions of school climate have been related to developmental competence, including positivity (Luengo Kanacri et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…School support is here defined as sustainable efforts developed by the school to support trauma-exposed youth. A study by Yablon ( 2015 ) showed the importance of a positive school climate as a resilience factor for explaining PTSD and posttraumatic growth in high school students living in an armed conflict zone. However, several studies report that teachers are uncertain of how to support children who have been exposed to trauma and facilitate the learning process in these situations (Alisic, Boeije, Jongmans, & Kleber, 2012 ; Dyregrov, Dyregrov, & Idsoe, 2013 ; Papadatou, Metallinou, Hatzichristou, & Pavlidi, 2002 ).…”
mentioning
confidence: 99%